Loyalist supergrass trials: an opportunity for open source intelligence?. Issue 7 (10th November 2019) - Monaghan, Rachel
ABSTRACT: In the 1980s some thirty members of paramilitary groups in Northern Ireland both republican and loyalist, agreed to provide evidence against their former colleagues in return for a reduced sentence or immunity from prosecution, a new identity and life. Such individuals became commonly known as 'supergrasses'. This article drawing on archival and documentary research explores the potential opportunity these supergrass trials provided for republican paramilitary groups to gather open source intelligence on their loyalist counterparts. It also tracks whether individuals named by loyalist supergrasses were subsequently targeted by opposing paramilitary groups on their acquittal or release from prison.